Effect of Price, Sales Promotion and Halal Awareness of Skin Care Product Purchase Decisions (Case Study on Shopee App Users in Jakarta) - Sadewa Assidiqi; Lia Siti Julaeha (International Journal of Education, Information Technology, and Others, 2021)
Indonesia is the country with the largest Muslim population in the world that will continue to grow and the country with the second largest consumption of cosmetics after India. Like the growing Muslim population, awareness of the use of halal products is also increasinglygrowing. This article aims to analyze the influence of price, sales promotion and halal awareness of purchasing decisions especially on halal cosmetic products. Thisresearch is quantitative research and cross sectional research with the period September 2020 - December 2020. A total of 124 respondents used the Bernoulli Formula. Primary data collection methods use questionnaires and analyzed using (SPSS) version 25, while secondary data is in the form of library studies. The results of this study are price, sales promotion and halal awareness partially and together affect the decision to buy skin care products in Shopee, meaning that if the price, promotion of sales and halal awareness increases, it will increase the purchase decision of skin care products in Shopee aplication